Influence Social Media Marketing to Brand Loyalty Through Customer Engagement on Local Products "Viva Cosmetics" - Widnyani, Ni Made; Rettobjaan, Vitalia Fina Carla; Astitiani, Ni Luh Putu Surya (Journal of Economics and Public Health, 2024)
This research aims to examine the impact of Social Media Marketing on Brand Loyalty through Customer Engagement on local products "Viva Cosmetics". The research design used is quantitative with an associative level of explanation. Research objects include Social Media Marketing, Brand Loyalty, and Customer Engagement, with research subjects being Viva Cosmetics users in Denpasar City, with a sample of 100 people. Data was collected using a questionnaire method, and analysis was carried out using Path analysis. The research results show that Social Media Marketing has a positive and significant effect on Customer Engagement, as well as an exclusive and significant effect on Brand Loyalty. Apart from that, Customer Engagement also has an exclusive and significant influence on Brand Loyalty. Furthermore, this research confirms that Social Media Marketing significantly influences Brand Loyalty through Customer Engagement